Komposisi Jenis Ikan di Perairan Pantai Teluk Saleh, Nusa Tenggara Barat (NTB) dan Tanimbar Utara, Maluku Tenggara - Langkosono Langkosono (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2004)
Study of the fish diversity in Saleh Bay, West Nusa Tenggara (NTB) has been carried out in August 2000, and in North Tanimbar, Maluku Tenggara   during November to  December 2002. The fishes  collecting in Saleh Bay using gillnet, beach seine, angling, and light fishing while in  North Tanimbar by beach seine. A total specimens which collected from Saleh Bay were 576 samples, consist of 108 species from 29 families while in North Tanimbar were found  2 763 specimens, representing 61 species from 28 families.